Comunidad Andina: ¿una organización compleja, cohesionada y coherente? - Tremolada Álvarez, Eric (2021)
Adding more than 50 years of Andean integration, it is worth asking how complex, cohesive and coherent is your organization? if you have achieved sufficient development and maturity,  what guarantees the effectiveness of its rules? and if the right produced by its organs is an immediate source of rights and obligations for all those affected? To answer these questions, we will go through the scientific theories of economic integration, through the structure of the Andean ordering system and its rules of application, and we will end up with its political institutions.